The genus Austrotinodes Schmid 1955 (Trichoptera: Ecnomidae) in Roraima state, Brazil: new records and description of a new species - Neto, Jaime De Liege Gama; Passos, Mahedy Araujo Bastos (Zootaxa, 2018)
A new species of Austrotinodes Schmid 1955 from Roraima state, Brazil is described and illustrated: Austrotinodes tepui sp. nov. In addition, A. lenti and A. neblinensis are recorded from Roraima state for the first time.